2021
DOI: 10.1002/oa.3031
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of birds at neolithic WF16, southern Jordan: Cut marks, body parts, and experimental skinning

Abstract: WF16 is an early Neolithic settlement in southern Jordan with a large bird bone assemblage (Number of Identified Specimens [NISP] = 7808), representing 18 families. We explore how the birds were utilized by considering cut marks and body part representation for each of the families represented, also drawing on the experimental skinning of buzzards, the most common bird in the assemblage. We conclude that the bird bones accumulated from a mix of activities including the exploitation of a seasonally abundant sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…An analysis of body parts and cut marks indicated that steppe buzzards had been brought to the settlement as whole carcasses. Some of these were skinned, as may have also been the case for honey buzzards and kites, and some were processed for consumption (White et al ., 2021b). Other large birds, including the lappet‐faced vulture, eastern Imperial, Bonelli's and Verreaux's eagles, were probably utilised for their plumage, as only their wing bones were present at the site, several with indicative cut marks.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…An analysis of body parts and cut marks indicated that steppe buzzards had been brought to the settlement as whole carcasses. Some of these were skinned, as may have also been the case for honey buzzards and kites, and some were processed for consumption (White et al ., 2021b). Other large birds, including the lappet‐faced vulture, eastern Imperial, Bonelli's and Verreaux's eagles, were probably utilised for their plumage, as only their wing bones were present at the site, several with indicative cut marks.…”
Section: Introductionmentioning
confidence: 99%
“…Although only eight specimens from MacQueen's bustard were recovered, this may have been a resident of Faynan and hunted primarily for food. Skeletal part frequencies also indicate that buzzards, kites and honey buzzards are likely to have been consumed (White et al ., 2021b). The bird bones were heavily concentrated in three structures, O45, O11 and O56 (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations